Characterisation of phenotypes of inflammation, fibrosis and remodeling in chronic rheumatic heart disease using multiparametric cardiovascular magnetic resonance and autophagy markers - Aremu, Olukayode Olasunkanmi (Department of Medicine, 2023)
Background: Rheumatic heart disease (RHD), concomitant to valvular damage, heart failure, arrhythmias and pulmonary hypertension is the major source of cardiovascular morbidity and mortality in the young, predominantly in low- and middle-income countries (LMICs). We investigated the association of valve lesions in RHD with cardiovascular magnetic resonance (CMR) tissue characteristics and autophagy markers, in this study. Methods: Forty-seven (47) patients (42 ± 12.8 years), with advanced RHD, awaiting valve replacement, confirmed on echocardiography, and matched with 30 healthy controls (39 ± 12.1 years), were scanned using a 3T Siemens Magnetom Skyra. CMR parameters were derived from the following acquisitions: cine imaging of the short and long axes, T1 mapping (MOLLI, 5(3)3, estimation of ECV and late gadolinium enhancement (LGE) imaging. For the cellular study, we analysed the immunoexpression of Beclin, LC3, p62, BAX, Bcl-2 and caspase-3 in patients confirmed with RHD and valvular heart disease